MILK CONSUMPTION IMPROVES THE NUTRITIONAL ADEQUACY OF 12-24 MONTHS OLD CHILDREN IN BEJI, DEPOK, INDONESIA - Syafiq, Ahmad; Septiani, Seala; Fikawati, Sandra; Qirani, Ida Ayu Devi (Ridwan Institute, 2025)
Background: Weaning period is crucial to ensure appropriate nutritional status. Proper complementary feeding can help children reach optimal growth. Milk as part of complementary feeding is evidently beneficial. The aim of this study was to determine difference in nutritional status between children who consumed milk as a part of complementary feeding and children who did not. Methods: Cross-sectional study was conducted on 102 children aged 12-24 months in Depok City. Data was obtained from height and weight measurements, 1x24-hour food recall, and validated semi-quantitative food frequency questionnaire. Results: Nutritional status of children who consumed milk was better at all indicators compared to those who did not, especially in length-for-age, shown by the stunting prevalence (not consuming 26.2%; consuming milk 19.5%). Children who consumed milk also had significantly higher nutrient adequacy. Nutrient intake of mothers who still provided breast milk which demand higher nutritional need, turned out to be lower than the requirements. Conclusion: Milk consumption might benefits children aged 12-23 months for their nutritional status and to meet their nutrients adequacy. Results are expected to be consideration to assess regulations related to milk promotion for children